Reproduction of Traditional Grid as a Change in Urban Transport Memory: What ‘Superblock’ Proposes in Barcelona - Erçetin, Cihan; Durmaz, Büşra (ICONARCH International Congress of Architecture and Planning, 2017)
Grid urban layout was preferred as an effective pattern for many ancient settlements and contemporary cities. Barcelona city has started to experience the plans focusing on grid layout together with Cerda's plan in 1850s in order to respond the question of urban growth. Today, Barcelona is considered one of the cities, which owns a spectacular reputation regarding its grid structure and Gaudi's architectural interventions in the city. In recent few years, policy makers in Barcelona have initiated a process to make changes as a solution in grid structure to make it work more effectively due to several problems. This solution is called new Superblock structure -a new public transport regulation on grid system which enables to make changes physically on Cerda's grid system-. Transition process of Barcelona from grid to Superblock pattern has been carried out with also a change in urban transport memory on the minds’ of inhabitants and tourists in the city. Here, what is meant by emphasizing transport memory is the existing perception of traditional grid and perception of prospective new Superblock design on transport pattern. In other words, existing transport memory is based more on car dependency due to current newly emerging congestion and pollution problems, and the contemporary Superblock design is expected to reveal a sustainable transport network with public transport walking and cycling.Superblock